ANALISIS TEORI HUMANISTIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Firdaus, Nazilatul Fatihah; Mukaffa, Zumrotul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the concepts and ideas of humanistic theory, examine humanistic theory in learning, and analyze its implementation in Islamic Religious Education learning. The study employed a qualitative approach using library research. Data were collected through documentation studies from various primary and secondary sources related to humanistic theory and Islamic Religious Education learning. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that humanistic theory is an approach that views humans as individuals who possess potential, freedom, self-awareness, and the ability to develop optimally through meaningful learning experiences. The ideas of humanistic figures such as Abraham Maslow, Carl Rogers, Rollo May, Arthur Combs, Malcolm Knowles, Benjamin Bloom, and David R. Krathwohl emphasize the importance of holistic human development encompassing cognitive, affective, and psychomotor aspects. In learning, humanistic theory positions students as the center of the educational process through dialogical, contextual, and self-development-oriented learning. The implementation of humanistic theory in Islamic Religious Education learning is relevant to the goals of Islamic education because it is not only oriented toward knowledge transfer but also toward character building, spiritual awareness, and the internalization of religious values in students’ daily lives. Therefore, the humanistic approach can serve as a foundation for creating Islamic Religious Education learning that is more humane, meaningful, and oriented toward the holistic development of students.